1986
DOI: 10.1093/oxfordjournals.pcp.a077123
|View full text |Cite
|
Sign up to set email alerts
|

A Parallel Study of Pigment Bleaching and Cytochrome Breakdown during Aging of Thylakoid Membranes

Abstract: Aging of freshly isolated thylakoid membranes from spinach leaves (Spinacia oleracea L.) leads to dramatic alterations in both the cytochrome (£559 (HP) andy") composition and pigment (chlorophylls a and b and /J-carotene) content. These changes occur at a faster rate under anaerobic conditions or after heating thylakoid membranes, and in light as well as in darkness. In addition, when thylakoid membranes are heated at 78°C for 8 min, or incubated in the presence of an emulsion of linoleic acid, a huge decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The yellowing of leaves is the most obvious visible senescence symptom resulting from the degradation of Chl and other components of chloroplasts that occurs in most leafy plants, including D. solida. Previous studies have reported that leaf senescence is also accompanied by the breakdown of Chl a and b [55], which involves non-enzymatic mechanisms [56,57] and multistep enzymatic mechanisms [52]. The former is associated with an increase in levels of reactive oxygen species (ROS) in leaves during senescence [57,58], and the latter is directly caused by the activities of Chl-degrading enzymes such as chlorophyllase, Mg-dechelatase, pheophorbide a oxygenase and red chlorophyll catabolite reductase [52].…”
Section: Discussionmentioning
confidence: 99%
“…The yellowing of leaves is the most obvious visible senescence symptom resulting from the degradation of Chl and other components of chloroplasts that occurs in most leafy plants, including D. solida. Previous studies have reported that leaf senescence is also accompanied by the breakdown of Chl a and b [55], which involves non-enzymatic mechanisms [56,57] and multistep enzymatic mechanisms [52]. The former is associated with an increase in levels of reactive oxygen species (ROS) in leaves during senescence [57,58], and the latter is directly caused by the activities of Chl-degrading enzymes such as chlorophyllase, Mg-dechelatase, pheophorbide a oxygenase and red chlorophyll catabolite reductase [52].…”
Section: Discussionmentioning
confidence: 99%